Efektifitas Saluran Promosi Melalui Media Sosial Instagram Di Kafe Green Kubu Tegalalang - I nyoman; I Nyoman, Arcana (JURNAL BISNIS HOSPITALITI, 2023)
Green Kubu Tegalalang Cafe, Gianyar, which is located in the northern hinterland of Gianyar regency, relies heavily on its promotional strategy through instagram social media. This study aims to determine the effect of the effectiveness of promotional channels through instagram on the marketing of Green Kubu Tegalalang Cafe, Gianyar. There were 100 respondents involved in this study. This study used a descriptive quantitative approach with five variables consisting of sixteen indicators. This study concluded that there are four variables of promotion through instagram that are very effective in attracting visitors, these include advertizing & sharing of content, sales promotion & online communities, credibility of public relation and publicity, online marketing & interaction, while the variables of accessibility, events and experiences obtained quite effective results. This research suggests that the manager of Green Kubu Tegalalang Cafe improve the quality of entertainment and organize events through collaboration with professional event organizers (EO) in order to improve image and expand the reach of market segments. This research also suggests that the Cafe supposed to maintains promotional content through instagram to maintain the company's image because these promotional channels are very attractive to potential visitors. Keywords: effectiveness, promotion, instagram social media.